Reactualizing the Meaning of Tasawuf: An Introduction to Education - Yasin Syafii Azami; Abid Nurhuda; Murjazin Murjazin (Nusantara Education, 2023)
Sufism is frequently perceived as a static and traditional discipline, often viewed as resistant to change and detached from contemporary intellectual developments. However, such assumptions overlook the dynamic nature of tasawuf, which demonstrates a capacity for adaptation and reinterpretation across different historical and socio-cultural contexts. This study aims to examine the essential meaning of Sufism from a terminological perspective, highlighting its conceptual flexibility and enduring relevance in guiding spiritual life. This research employs a qualitative approach using a literature study method. Data were systematically collected from classical and contemporary sources on Sufism, including theological, philosophical, and ethical discourses. The collected materials were then analyzed through content analysis to identify patterns, variations, and underlying principles in defining Sufism. This method enables a comprehensive understanding of how Sufism has been articulated by various scholars and traditions. The findings reveal that the essence of Sufism cannot be confined to a single, fixed definition. Instead, it is shaped by diverse perspectives, each emphasizing different dimensions such as spiritual purification, ethical refinement, and experiential knowledge of the Divine. Despite these variations, all interpretations consistently root their foundations in the Qur'an and Sunnah. Sufism also encompasses a distinct spiritual orientation that focuses on cultivating an intimate relationship with God, often expressed in the principle “Ilāhī anta maqṣūdī wa riḍāka maṭlūbī” (O God, You are my ultimate goal, and Your pleasure is what I seek). This study contributes to the scholarly discourse by reaffirming the adaptive and contextual nature of Sufism, challenging its stereotypical portrayal as rigid and outdated. It offers a nuanced understanding that positions Sufism as a living tradition capable of engaging with modern spiritual and intellectual challenges.